Measuring vibration and noise of blower based on different operation modes - Syaza Mawaddah Binti Zul Azki (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Excessive operational period of blower will lead the workers to excessive exposure of vibration and noise. As the vibration and noise exposure continues, the pain may lead to a permanent injury or disability. Several factors contribute to the vibration transmitted to the hand and the noise exposure such as operator's posture, working conditions, individual factors and etc. A very few studies have been carried out to investigate the effect of the operation conditions of a power hand tool on its vibration emission. Therefore, this project covered on vibration and noise of the blower to determine the standardised working conditions (based on engine speed and sway of angle while operating) which the measurement was carried out. The project was started with machine preparation followed by the design of measurement systems by LabVIEW. Next, the machine was operated based on parameters and mode operations and vibration and noise of the blower was measured by using the design measurement systems.From the experiments, the graphs were formed based on the data collected. The mode operation of 6500 rpm with 45dӨd 90 exhibited the highest vibration and noise level. From the results, it shown that the engine speed was important operating parameter that can affects Hand Arm Vibration (HAV) and Noise Induced Hearing Loss (NIHL). The operator should avoid operating the blower with full throttle which is 6500 rpm at the sway angle of 45d Ө d90 as it will increase the risk of getting HAV syndrome and NIHL.